(untitled) (Revista Argentina de Musicología, 2026)
This study evaluates the induction of Musical Creation Techniques (Técnicas de Creación Musical, TCM) in improvisation and collective creation groups, through the identification of characteristics in the musical creations recorded in audio and the aspects of their production. TCM are a set of strategies that apply concepts of structural optimization, timing, and perceptual balance, designed for the coordination of musicians in an improvisation or collaboration, favoring the collective musical arrangement based on individual resources. Between 2006 and 2018, TCM were implemented in workshops and public performances involving 400 participants, from amateurs to professionals, in urban and community settings. As evidence, 1,142 musical creations recorded in audio were produced, which were classified and analyzed based on their achievement of structural coherence. To evaluate creative production, criteria used in computational creativity are incorporated here, including the SPECS procedure, linguistic evaluation, and other contributions related to creative production. The findings confirm that TCMs promote structured improvisation, allowing both novice and experienced musicians to create appealing musical pieces on the spot. This analysis provides evidence regarding the optimized structures proposed in theory, which foster group musical creativity through cooperation tactics. Editorial History: Received: April 12, 2025 Accepted: November 1, 2025